THE MORPHOLOGICAL FEATURE FORMATION OF PHRASEOLOGICAL UNITS IN ENGLISH AND UZBEK (International journal of artificial intelligence, 2026)
Phraseological units (PUs), also known as idioms, fixed expressions, collocations, and proverbs, represent stable, figurative combinations of words that function as single lexical units with partially or fully reinterpreted meanings. This article examines the morphological features involved in their formation, stability, variability, and transformation in English (an analytic Indo-European language) and Uzbek (an agglutinative Turkic language). Drawing on structural-semantic classifications by V.V. Vinogradov and A.V. Kunin, as well as Uzbek scholarly traditions, the study highlights differences arising from typological contrasts: English PUs exhibit limited morphological flexibility due to analytic structure and reliance on word order, while Uzbek PUs demonstrate greater integration with agglutinative morphology yet maintain strict stability through fixed grammatical forms. The analysis reveals shared universal traits (stability, reproducibility, idiomaticity) alongside language-specific formation processes, such as morphological transformations (e.g., changes in tense, number, or affixes) and variants. Comparative examples illustrate how morphological integrity contributes to cultural expressiveness and challenges in translation. The findings underscore the role of morphology in PU formation for cross-linguistic studies, lexicography, and language pedagogy.